Development of Interactive Learning Media Based on Articulate Storyline for Teaching Mathematics on Plane Shapes for Grade IV at SDN Baru 02 Pagi - Viola Meika Putri; Kowiyah Kowiyah (Eduvest - Journal of Universal Studies, 2024)
This study aims to develop interactive learning media based on Articulate Storyline as a medium for learning mathematics flat building material, and to determine the quality of products that have been made so that they are feasible and interesting to use in learning activities with the Research and Development (R & D) research and development method which refers to the ADDIE model or 5 stages in the form of analysis, design, development, implementation and evaluation. The subjects of this study were 25 fourth grade students. The data collection techniques used were observation and questionnaire. Data collection instruments with media validation sheets, material validation sheets, language validation sheets, teacher validation sheets, student response questionnaires. The results of the assessment from the experts are among others: the percentage of media experts 86% shows the criteria "very feasible", material experts 95% shows the criteria "very feasible", language experts 89% shows the criteria "very feasible", the results obtained by the teacher 92% shows the criteria "very feasible". The results of the small group trial get a percentage of 92% and the large group trial describes a percentage of 91% and describes the criteria "very feasible". Based on the results of the research data, it shows that Articulate Storyline Media becomes a media for learning mathematics theory of flat buildings that is very feasible and interesting to use.